2006
DOI: 10.2193/0091-7648(2006)34[656:coteap]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effects and Performance of Four Types of Radiotransmitters for Use With Scoters

Abstract: Radiotransmitters are widely used in wildlife ecology, often providing data that cannot be collected using other methods. However, negative effects have been associated with the use of transmitters for some species. We evaluated the effects and performance of 4 radiotransmitter types for use with surf and white‐winged scoters (Melanitta perspicillata and M. fusca): COEXT—coelomically implanted transmitters with external antennas, COINT—coelomically implanted transmitters with internal antennas, SUBCU—subcutane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 22 publications
1
39
0
Order By: Relevance
“…The reduction in short-term survival rates of female Mallards of up to 23% in Paquette et al [60], which was only significant in one out of five study sites, indicated that tags attached with subcutaneous anchors may sometimes affect adult birds. Other studies using subcutaneous implants found no effect on short-term survival of Lesser Scaups Aythya affinis [12], Surf Scoters Melanitta perspicillata and White-winged Scoters Melanitta deglandi [40] or on annual survival of Wood Ducks Aix sponsa [36]. Subcutaneous attachments have been found to negatively affect reproduction in some cases.…”
Section: Subcutaneous Attachmentsmentioning
confidence: 99%
“…The reduction in short-term survival rates of female Mallards of up to 23% in Paquette et al [60], which was only significant in one out of five study sites, indicated that tags attached with subcutaneous anchors may sometimes affect adult birds. Other studies using subcutaneous implants found no effect on short-term survival of Lesser Scaups Aythya affinis [12], Surf Scoters Melanitta perspicillata and White-winged Scoters Melanitta deglandi [40] or on annual survival of Wood Ducks Aix sponsa [36]. Subcutaneous attachments have been found to negatively affect reproduction in some cases.…”
Section: Subcutaneous Attachmentsmentioning
confidence: 99%
“…The VHF radiotransmitters, weighing <12 g (-1% of average molting body mass), were attached using subcutaneous prongs and superglue (Iverson et al 2006). The foraging effort of each radiomarked individual was monitored multiple times throughout remigial molt for 1-h intervals during different parts of the day, including nocturnal observations.…”
Section: Methodsmentioning
confidence: 99%
“…The birds were implanted with PTT satellite-transmitters following standard procedures (Mulcahy & Esler 1999). The implantation method has been shown to perform well for scoters (Iverson et al 2006). Birds were released after a recovery period of at least 1 h. Individuals that did not leave winter areas, died, or experienced radio failure during migration were not included in analyses.…”
Section: Captures and Fitting Of Transmittersmentioning
confidence: 99%